(untitled) (jornal of the libyan geographical society, 2009)
The dissolution of algal rock layers by water results in a set of unique geomorphological phenomena in their forms and types, known as Karst phenomena, which are depressions formed as a result of the dissolution of limestone formations. This is due to the combination of carbon dioxide with water. Karst sinkholes, or karst sinkholes, which are depressions in limestone formations through which rivers and waterways penetrate into the rock, are among the most common geomorphological features in such formations. Karst sinkholes are divided into two types: the first is known as dissolution sinkholes, which form over many years without affecting the rock structure. The second type is known as collapse sinkholes, which form as a result of the collapse of surface limestone.